Pengaruh Pembelajaran Berbasis Multimedia Interaktif terhadap Peningkatan Motivasi dan Hasil Belajar IPA Kelas V MI Wahid Hasyim Bakung (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The impact of suboptimal learning contributes to low student learning outcomes. An additional factor influencing these low scores is students' difficulty in understanding material that is purely descriptive or conceptual. The application of interactive multimedia in learning has significant potential to improve the desired thinking skills. This study aims to describe and analyze the effect of the implementation of interactive multimedia-based learning on student learning motivation and learning outcomes. This study uses an experimental quantitative method. Data collection techniques include interviews, observations, and documentation. Data analysis is carried out through testing the validity and reliability of the instrument for each question item using the SPSS program, as well as descriptive analysis techniques. The calculation results from SPSS IBM 21 show that based on the hypothesis test through the summary model and ANOVA, the correlation value is 0.930, while the R square value of 0.865 indicates that the interactive multimedia variable has an influence of 86.5% on the learning motivation and learning outcomes variables. The results of the ANOVA test show a significance value of 0.000, which is smaller than 0.05, so the null hypothesis (H0) is rejected and the alternative hypothesis (HA) is accepted. Thus, it can be concluded that there is a significant influence of interactive multimedia variables on learning motivation and learning outcomes.